Bilingualism, Multilingualism and Translingualism as Problems of Modern Culture - S. Y. Dianina (Концепт: философия, религия, культура, 2022)
On December 3-4, the Faculty of Humanities and Social Sciences of the People’s Friendship University of Russia (RUDN University), in cooperation with Al-Farabi Kazakh National University and the University of Texas at San Antonio, held the 7th International Conference Bilingualism, Multilingualism, Translingualism and Language Education. This unique research and practice project on bilingualism in post-Soviet countries takes place under the guidance of the International Association of Teachers of Russian Language and Literature (IATRLL). The initiators and hosts of the Conference are professors of the RUDN University U. M. Bakhtikireeva and V. P. Sinyachkin. The Conference opened with the speeches of A. V. Dolzhikova (Institute of Russian Language, RUDN University), N. S. Trukhanovskaya (Ministry of Science and Higher Education), S. Kellman (University of Texas), E. D. Suleimenova (Kazakhstanian ATRLL), L. G. Balasanian (Armenian ATRLL). Plenary papers concerned the issues of language crosscultural development, bilingualism, translation in intercultural communication. One of the key topics was the transformation of the institutional language discourse and its impact on education policy. Thematic sessions elaborated on these problems and covered the history and reality of group and individual bilingualism, theory and practice of language teaching and translation. Participants of the Knowledge Transfer workshop discussed possibilities of a systemic approach to teaching Russian for native and non-native speakers. Researchers and language teachers had a great opportunity to share their academic and practical expertise on language education and intercultural communication. In line with the previous conferences, theoretical issues of bilingualism, the study and description of its features attracted considerable attention. The Conference attracted specialists in numerous fields and served as a venue for cooperation: bilingualism today needs further discussion and searching for new answers to the long-standing questions.